(untitled) (Journal of Laboratory Animal Science, 2024)
Recently procured New Zealand White rabbits were brought to the department and kept for quarantine in the animal house facility. Out of 5 rabbits, one rabbit was anorexic, corner seating setting, and could not respond to the physical stimuli. On physical examination, we found the raised subcutaneous nodule covered under fur at lateral side of the face. PET CT imaging was done which indicated the central area of dead tissue with peripheral uptake of 18F-FDG. Fine needle aspiration was performed and collected sample was subjected for bacteriology and cell cytological examination. Cell cytology showed many degenerated heterophils, few RBC’s, and other cellular debris. Predominantly Klebsiella and few Escherichia coli bacterial colonies were grown on agar. A broad spectrum Enrofloxacin antibiotic was given to the other animals as a preventive measures to control the infection